2014
DOI: 10.1016/j.ejca.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Safety of cabazitaxel in senior adults with metastatic castration-resistant prostate cancer: Results of the European compassionate-use programme

Abstract: The results suggest that cabazitaxel has a manageable safety profile in everyday clinical practice. Prophylactic use of G-CSF, especially at cycle 1 and in men aged > or =75 years, is important and improves tolerability in senior adults treated with cabazitaxel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
71
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 31 publications
7
71
1
8
Order By: Relevance
“…Non-hematological adverse events of Grade ≥3 occurred at a similar manageable frequency in our study compared to previous EAP reports 11,[14][15][16][17][18] and the TROPIC trial. 9 Overall, this EAP study has demonstrated that cabazitaxel in routine clinical practice has a manageable safety profile that does not appear to be impacted by the prior use of abiraterone acetate.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…Non-hematological adverse events of Grade ≥3 occurred at a similar manageable frequency in our study compared to previous EAP reports 11,[14][15][16][17][18] and the TROPIC trial. 9 Overall, this EAP study has demonstrated that cabazitaxel in routine clinical practice has a manageable safety profile that does not appear to be impacted by the prior use of abiraterone acetate.…”
supporting
confidence: 51%
“…Other published EAP reports have shown the rates of Grade 3 or higher neutropenia range from 33.9-4.1% 14,15,18 with prophylactic use of G-CSF in 16.3-62.4% 14,15,18 of patients. Non-hematological adverse events of Grade ≥3 occurred at a similar manageable frequency in our study compared to previous EAP reports 11,[14][15][16][17][18] and the TROPIC trial.…”
mentioning
confidence: 99%
“…Отмечено, что профилактическое ис-пользование Г-КСФ со 2-го по 10-й циклы терапии позволило вдвое снизить частоту развития нейтропе-нии ≥III степени тяжести (44,6 % против 24,7 %). Бо-лее того, при анализе частоты развития нежелательных реакций у пациентов, получавших кабазитаксел в стандартной дозе в рамках европейской программы расширенного доступа (746 пациентов из 20 стран Ев-ропы), было выявлено, что нейтропения ≥III степени тяжести развивалась всего у 17,0 % пациентов, лейко-пения -у 7,4 %, фебрильная нейтропения -у 5,4 %, анемия -у 4,7 %, тромбоцитопения -у 1,1 % [46]. При этом 44 % пациентов, получавших кабазитаксел, были старше 70 лет.…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
“…При этом 44 % пациентов, получавших кабазитаксел, были старше 70 лет. Авторы связали более низкую ча-стоту токсичности кабазитаксела в программе расши-ренного доступа по сравнению с исследованием TROPIC с тем, что в рамках этой программы были рекомендованы проактивный менеджмент нежела-тельных реакций и профилактическое и терапевтиче-ское использование Г-КСФ начиная с 1-го курса химиотерапии [46].…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
“…Однако для первых были ха-рактерны более высокие показатели частоты развития нежелательных явлений и редукции дозы исследуемо-го препарата [5][6][7][8]. Разграничение по возрасту между молодыми и пожилыми пациентами было установлено на уровне 75 лет.…”
Section: Introductionunclassified